Developing Peer Corrective Skills in Business Letter Writing in English as a Foreign Language - Monta Farneste; Olga Pašinska (Baltic Journal of English Language, Literature and Culture, 2019)
Peer corrective feedback (PCF) implementation is a topical issue in writing skills development at tertiary level. Those researchers who explore the application of PCF in higher education (e.g. Liu and Sadler, 2003; Hyland, K. and Hyland, F., 2006) admit that students face difficulties in providing qualitative feedback that determines the effectiveness of this teaching tool. Therefore, the goal of this paper was to investigate what actions could be taken in order to develop students’ PCF skills and, consequently, foster the quality of PCF. The primary research method was a case study in which the participants were 24 second-year undergraduates majoring in English as a Foreign Language (EFL) at a university in Latvia. The materials of the case study involve the genre of a business letter, which plays a vital role in people’s professional and everyday life. The results of the research revealed that providing students with an assessment scale and teaching how to apply it increase the quality of PCF.